Sustainable wet-spun cellulose-Moringa oleifera composite fibres for potential water purification - Orisawayi, Abimbola Oluwatayo; Boylla, Prithivi; Koziol, Krzysztof K.; Rahatekar, Sameer S. (Royal Society of Chemistry (RSC), 2025)
This study explores a pioneering fabrication of novel cellulose-Moringa oleifera (M. oleifera) composite fibres (CeL-MoFs) and comparable pure regenerated cellulose fibres (CeFs) using the ionic liquid 1-ethyl-3-methylimidazolium diethyl phosphate (EMIM DEP) and the simple traditional wet-spinning process. The composites, CeL-MoFs at 0.5%, 1%, 2%, and 3%, were characterised. Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) confirmed the successful integration of M. oleifera seed powder (MoP) into the cellulose matrix. The results of preliminary adsorption studies demonstrated high selectivity for copper ions (Cu2+), with no detectable selectivity towards nickel (Ni2+) or cadmium (Cd2+). Thermogravimetric analysis (TGA) and derivative thermogravimetric (DTG) analysis revealed thermal stability variations with increasing MoP content, while atomic force microscopy (AFM) showed surface roughness and fibre defects. Rheological testing validated spinnability, and tensile analysis identified CeL-MoFs (2%) as the optimal composite, balancing mechanical strength and adsorption efficiency. These novel CeL-MoF composites, fabricated using EMIM DEP, are proposed as scalable, eco-friendly materials for selective heavy metal removal. Future work will focus on adsorption kinetics, thermodynamic modelling, and scaling production for industrial water purification applications.
Keywords: 34 Chemical Sciences; 7 Affordable and Clean Energy; 34 Chemical sciences